2017
DOI: 10.1073/pnas.1616543114
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory cascade and biological activity of Beauveria bassiana oosporein that limits bacterial growth after host death

Abstract: The regulatory network and biological functions of the fungal secondary metabolite oosporein have remained obscure. Beauveria bassiana has evolved the ability to parasitize insects and outcompete microbial challengers for assimilation of host nutrients. A novel zinc finger transcription factor, BbSmr1 (B. bassiana secondary metabolite regulator 1), was identified in a screen for oosporein overproduction. Deletion of Bbsmr1 resulted in up-regulation of the oosporein biosynthetic gene cluster (OpS genes) and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
129
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(132 citation statements)
references
References 52 publications
2
129
0
1
Order By: Relevance
“…A few secondary metabolites produced by insect-pathogenic fungi have been established to contribute to fungal virulence against insect hosts such as the destruxins produced by Metarhizium species (27) and the beauvericin and oosporein biosynthesized by Beauveria bassiana (28, 29). The oosporein produced by Beauveria could also help the fungus to outcompete bacterial growth during fungal colonization of insect hosts (30, 31). Consistent with the immune inhibition and insecticidal effect of CsA on insects (16, 32), our insect bioassays revealed that abolishment of CSN production impaired fungal virulence against insect hosts.…”
Section: Discussionmentioning
confidence: 99%
“…A few secondary metabolites produced by insect-pathogenic fungi have been established to contribute to fungal virulence against insect hosts such as the destruxins produced by Metarhizium species (27) and the beauvericin and oosporein biosynthesized by Beauveria bassiana (28, 29). The oosporein produced by Beauveria could also help the fungus to outcompete bacterial growth during fungal colonization of insect hosts (30, 31). Consistent with the immune inhibition and insecticidal effect of CsA on insects (16, 32), our insect bioassays revealed that abolishment of CSN production impaired fungal virulence against insect hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the ΔBbThm1 showed only mild to moderate effects to other stress phenotypes, that is, oxidative, osmotic and/or general growth, these data suggest that heat and/or detergent susceptibility reflect critical specific factors contributing to infection, a finding that has not been previously reported and/or known to be important for successful mycosis by this pathogen. To the best of our knowledge to date, only one other Gal4-like TF has been substantially characterized in entomopathogenic fungi, namely the Ops3 TF that is part of and a regulator of the oosporein secondary metabolite gene cluster Fan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Infection occurs via adhesion of fungal conidia to the cuticle of the insect and subsequent direct penetration of the exoskeleton (Ortiz-Urquiza and . Penetrating hyphae elaborate in vivo hyphal bodies that proliferate within the host hemocoel, ultimately growing from the inside out to sporulate on the host cadaver Wanchoo et al, 2009;Fan et al, 2017). For most susceptible insects, death typically occurs within 3-6 days of post-infection, although significant variation can be seen between different hosts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungi are known producers of a broad array of structurally diverse NRPS‐derived natural products, which include immunosuppressant cyclosporine from Tolypocladium inflatum , insecticidal destruxin from Metarhizium anisopliae , xyloallenolide A containing an aromatic allenic ether moiety from a mangrove‐associated Xylaria sp. 2508, and insecticidal and antitumor bassianolide and beauvericin from Beauveria bassiana . We recently reported the isolation of antibacterial tetracyclic peptides named pseudoxylallemycins A–F ( 1 – 6 ) from the stowaway fungus Pseudoxylaria sp.…”
Section: Introductionmentioning
confidence: 99%